1997
DOI: 10.1002/(sici)1098-2744(199703)18:3<142::aid-mc3>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of G1 cyclins and cyclin-dependent kinases during tumor progression of chemically induced mouse skin neoplasms

Abstract: Cyclins and cyclin-dependent kinases (Cdks) are central to regulation of the cell cycle. Their abnormal expression may cause loss of cell-cycle control and result in autonomous cell growth, a critical feature of neoplasias. In this study, using immunoblotting, we analyzed the protein levels of several G1/S cyclins (cyclins D1, D2, D3, A, and E) and their respective Cdks (Cdk 2, 4, and 6) in 17 mouse squamous cell carcinomas (SCCs) and 18 mouse skin tumor cell lines. Overexpression of these cell cycle-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
4
29
0
Order By: Relevance
“…Cyclin D1 is constitutively overexpressed in 100% of mouse skin papillomas and squamous cell carcinomas obtained by DMBA/TPA treatment protocols. Moreover, E2F1 protein levels have been shown to be elevated in mouse skin papillomas and squamous cell carcinomas (Zhang et al, 1997). Thus, overexpression of E2F1 in our transgenic lines mimics in some ways what is seen during mouse skin carcinogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…Cyclin D1 is constitutively overexpressed in 100% of mouse skin papillomas and squamous cell carcinomas obtained by DMBA/TPA treatment protocols. Moreover, E2F1 protein levels have been shown to be elevated in mouse skin papillomas and squamous cell carcinomas (Zhang et al, 1997). Thus, overexpression of E2F1 in our transgenic lines mimics in some ways what is seen during mouse skin carcinogenesis.…”
Section: Discussionsupporting
confidence: 58%
“…Although alteration in cell-cycle regulatory machinery in this model was previously reported (Zhang et al, 1997), this is the ®rst sequential study of the alterations in cell-cycle protein expression during the premalignant progression of epidermal lesions. In this study, we used the two-stage carcinogenesis model to determine the expression of cell-cycle proteins during promotion and papilloma progression in SENCAR mice.…”
Section: Introductionmentioning
confidence: 77%
“…The relative abundance of each protein at each stage was determined from the absorbance of each band and normalized against PCNA expression in the same sample. Statistical analysis showed signi®cant di erences in the four members of the E2F family (E2F-1 P50.0001; E2F-2 P50.03; E2F-4 P50.0001, and E2F-5 P50.0001) during promotion and between papillomas of 10 and 20 weeks of promotion (E2F-1 P50.0001; E2F-2 P40.03, E2F-4 P40.001, and E2F-5 P40.001) (b) to play distinct roles by inducing the expression of di erent genes that participate in G1/S phase transition (De Gregori et al, 1997;Zhang et al, 1997). We analysed the protein levels of E2F-1, E2F-2, E2F-4 and E2F-5 during mouse skin promotion by Western blotting.…”
Section: Expression Of Rb Family Proteins and E2f Transcription Factorsmentioning
confidence: 99%
“…Accumulation of this complex leads to the activation of the kinases that phosphorylate and inactivate the tumor suppressor retinoblastoma, a necessary step for cell cycle progression through G1-to-S phases (Harbour and Dean, 2000). The expression levels of cyclin D1 have been shown to be rate limiting in cellular proliferation induced by a variety of stimuli (Ohtsubo and Roberts, 1993;Quelle et al, 1993;Albanese et al, 1995;Watanabe et al, 1996), and an increased expression of cyclin D1 has been observed in several tumors (Wang et al, 1994;Arber et al, 1996;Zhang et al, 1997;Albanese et al, 1999).…”
Section: Introductionmentioning
confidence: 99%